Pengaruh Aromaterapi Mawar Terhadap Peningkatan Kualitas Tidur Pada Lanjut Usia - Purnama Sari, Reni; , Yulisna Mutia Sari, SST., M.Sc. (GRS); , Umi Budi Rahayu, SST.FT, S.Pd.,M.Kes (2015)
Background of the research : aging is a dynamic and complex result from cells changing, fisiological and psycological. Elderly closely related to many changing cause of aging process, like the change of anatomy / fisiologic, kind of disease and pathologic condition as the impact of aging. Also the influence of psychosocial in organ function, the increase of elderly population have the impact to the elderly condition such as easy to stress and hard to sleep(imsomnia). Purpose of the research : to know the influence of rose therapy aroma toward the increase of sleeping quality of elderly Research method : this research is a quasi experimental research, with a pre and post method and control group design, it is a sample toward treatment group with rose therapy aroma in the rest room before go to bed for seven days long. While the control group watched for seven days long without using rose therapy aroma. The measurement of sleeping quality using PSQI(The Pitssburgh Sleep Quality Index). The data technique analysis use Wilcoxon Test. The result of the research : there is the influence of rose therapy aroma to increase the sleeping quality toward elderly with treatment group result 14,71 and the control group 12,43. After statisctic test using Wilcoxon can be found p-value: 0,018 in the treatment group while p-value=0,705 in the control group. Different influence test uses Mann Whitney with p-value=0,004. Conclusion : there is the influence of rose therapy aroma to increase of sleeping quality toward elderly.